GENERASI MUDA DAN DAKWAH: PERAN STRATEGIS DALAM PENGEMBANGAN MASYARAKAT - Fahma Islami (Department of Islamic Community Development, Faculty of Da'wah, State Islamic University (UIN) of Sultan Maulana Hasanuddin Banten, 2019)
The young generation in a broad sense, includes the ages of children and adolescents, from birth to maturity in all aspects (physical, spiritual, social, cultural and economic). This article aims to identify the role of the younger generation in da'wah in the field of community development, and identify methods and techniques of da'wah in community development. The research method used in this study is a qualitative approach. This study resulted in the findings that the role and function of young people occupy an important position in social life. This young generation is the hope of its former people to continue the struggle for da'wah like the deceased religious leaders. Generations of young Muslims and Muslim women who still have the spirit of preaching, strong bodies, and clear working brains are very helpful in improving the quality of human preaching and even maintaining the quality of an almost extinct civilization. Furthermore, in community development it is very important to study the influence of religion on the improvement of people's lives. There are three aspects that need to be studied, namely culture, social systems, and personality. These three aspects are complex and integrated social phenomena whose effects can be observed on human behavior which will facilitate the process of community development. The conclusion of this study finds that it is undeniable that the younger generation really has to become a reliable dakwah drafter in overcoming problems in society that arise and contribute to people's lives.